2013
DOI: 10.1016/j.cej.2013.07.019
|View full text |Cite
|
Sign up to set email alerts
|

Visible light responsive titania photocatalysts codoped by nitrogen and metal (Fe, Ni, Ag, or Pt) for remediation of aqueous pollutants

Abstract: Various cation and nitrogen doped and codoped TiO 2 photocatalysts, such as N-TiO 2 , Pt-TiO 2 , N-Fe-TiO 2 , N-Ni-TiO 2 , NAg -TiO 2 and N-Pt-TiO 2 , were prepared by an acid-catalysed sol-gel process. The photocatalysts were characterised by X-ray diffraction (XRD), nitrogen adsorption-desorption isotherms, UV-visible diffuse reflectance absorption spectroscopy (UV-vis DRS), and X-ray photoelectron spectroscopy (XPS). The activities of the photocatalysts were evaluated in photodegradation of phenol solutions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
29
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 96 publications
(34 citation statements)
references
References 58 publications
2
29
0
3
Order By: Relevance
“…It was found that all samples calcined at 400°C were of anatase phase. Compared to highly crystalline anatase TiO 2 , (103) and (112) crystal faces did not grow very well, which commonly occurred in TiO 2 calcined below 500°C (Sun et al 2013). …”
Section: Resultsmentioning
confidence: 96%
“…It was found that all samples calcined at 400°C were of anatase phase. Compared to highly crystalline anatase TiO 2 , (103) and (112) crystal faces did not grow very well, which commonly occurred in TiO 2 calcined below 500°C (Sun et al 2013). …”
Section: Resultsmentioning
confidence: 96%
“…Pillared clays, zeolites, mesoporous metal oxides, polymers and metal-organic frameworks have shown varying effectiveness in removing toxic pollutants [6]. However, most traditional adsorbents and catalysts are metal-based materials [7][8][9][10] and the demerits of high-cost, scarcity in nature and metal leaching of those materials were experienced [11]. Metal-free carbon materials for adsorption and catalytic oxidation are expected to overcome the issues.…”
Section: Introductionmentioning
confidence: 98%
“…[4,5] In development of heterogeneous photocatalysis for environmental remediation, metal oxides (TiO 2 , ZnO or Ta 2 O 5 , etc. ), [6,7] metal sulfides (CdS, ZnS or CuS 2 , etc. ), [8] and noble metals (Au, Ag and Pt, etc.…”
Section: Introductionmentioning
confidence: 99%